Mining Sector Under New Law of Decentralization: A Lesson from Some Districts in Central Java Province - Alfirdaus, Laila Kholid (Political Science Program, Universitas Negeri Semarang, 2019)
Under the new law of decentralization, namely Law No. 14/2014 on Local Governance, the national government shifts the governance of three main sectors related to natural resources from being city or regency’s authority to be the provincial government’s domain. This paper discusses possible advantages and drawbacks of the law in local level in the mining sector. This paper compares cases in Kebumen, Pati and Rembang in Central Java province to see the complexities of mining policy prior and after the issuance of the new law based on document analysis and interviews with local government apparatus and people concerned with mining issue in the local areas. While Law No. 4/2009 on non-oil mining strongly asserts the role of the district government, Law No. 14/2014 asserts that mining sector together with marine/fisheries and forest policy no longer become regency’s policy domain. They are withdrawn to be the provincial government’s authority. The former law was issued to respond to the strengthening demand of decentralization from the local regions but then was proven to merely result in the rising of new oligarchs in local mining governance. The later was meant to be a revision for the past. Yet, after about four years implemented, it is not free from other potentials of problems and complexities. Learning from the stagnancy of the mining problems in Central Java, it is clear that clarifying each government institution’s roles, and strengthening inclusion from the people are crucial.